The masking breakdown point of multivariate outlier identification rules - Claudia Becker; Ursula Gather (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 1997)
In this paper, we consider one-step outlier identification rules for multivariate data-generalizing the concept of so-called a - outlier identifiers_ as presented in Davies and Gather (1993) for the case of univariate samples. We investigate how the finite sample breakdown points of estimators used in these identification rules influence the masking behaviour of the rules.
Keywords: 519; Breakdown points; Outlier identification; Masking Robust statistics